A practical view of immunotherapy for food allergy - Tae Won Song (Korean Pediatric Society, 2016)
Food allergy is common and sometimes life threatening for Korean children. The current standard treatment of allergen avoidance and self-injectable epinephrine does not change the natural course of food allergy. Recently, oral, sublingual, and epicutaneous immunotherapies have been studied for their effectiveness against food allergy. While various rates of desensitization (36% to 100%) and tolerance (28% to 75%) have been induced by immunotherapies for food allergy, no single established protocol has been shown to be both effective and safe. In some studies, immunologic changes after immunotherapy for food allergy have been revealed. Adverse reactions to these immunotherapies have usually been localized, but severe systemic reactions have been observed in some cases. Although immunotherapy cannot be recommended for routine practice yet, results from recent studies demonstrate that immunotherapies are promising for the treatment of food allergy.